Determinants of Indonesian SMEs’ Intentions to Adopt Fintech: an Innovation Diffusion Theory Perspective - Bailusy, Muhsin N.; Pollack, Julien; Fahri, Johan; Amarullah, Dudi; Buamonabot, Irfandi (Journal of Indonesian Economy and Business, 2025)
Introduction/Main Objectives: Financial technology (Fintech) has become a solution for many SMEs seeking to improve business performance in an increasingly competitive business environment. Thus, it is important to investigate the factors underlying SMEs’ decision to adopt Fintech. Background Problem: Previous studies have applied various theoretical frameworks to explore Fintech adoption. Despite this, limited knowledge exists regarding the determinants influencing the adoption of Fintech among SMEs. Novelty: By using innovation diffusion theory, this study examines the underlying elements that contribute to the adoption of Fintech by SMEs. Research Methods: Data were collected using the survey approach. Self-administered questionnaires were distributed to SMEs in Indonesia using purposive sampling, yielding 273 responses. The data were then analyzed using the partial least square structural equation modelling (PLS-SEM) method. Findings/Results: The results confirmed all hypotheses developed for the study. Specifically, relative advantage, compatibility, complexity, and observability positively affect attitude towards Fintech adoption. In turn, positive attitude towards the adoption of Fintech has a significant impact on the intention to use Fintech. In addition, attitude mediates the relationship between IDT factors (relative advantage, compatibility, complexity, and observability) and Fintech adoption intention. Conclusion: Innovation diffusion theory is able to explain the factors that form SMEs' attitude and adoption intention toward Fintech. The outcomes of this research provide important implications both theoretically and practically.